A persistência de Jeca Tatuzinho: igual a si e a seu contrário - Piccino, Evandro Avelino (2018)
The central idea of this dissertation is that a significant portion of the explanation of permanence of Jeca Tatu as an integral part of the cultural history of Brazil is in one of its representations, the one contained in the advertising booklet Jeca Tatuzinho. Created by Monteiro Lobato, sponsored by Instituto Medicamenta Fontoura, published in 35 different editions between 1926 and 1973, as well as later versions on the comic format, Jeca Tatu, properly sanitized, became the first and most important advertising character created in Brazil. In the fleeting advertising time, Jeca Tatuzinho is a milestone because it resisted time and the temporary kept following as a permanent reference. His career is chronicled in details considering: (1) the objective circumstances that define the process for approval and publication of advertisement parts; (2) the evolution from the point of view of Lobato on his hillbilly, originally conceived as a “bush burner”; (3) the implications of the involvement of the writer with the interests of sanitarians / hygienists / eugenists Artur Neiva, Belisário Pena e Renato Khel; (4) the profiles of Lobato as a publicist and adman; (5) the relation between Jeca Tatu from Jeca Tatuzinho’s publications and the different representations of Jeca that came before and coexisted with him – on popular poetry, music, caricature and films; (6) the relationship between Monteiro Lobato and Candido Fontoura; (7) the relations that Roger Chartier established between the “materiality of text and textuality of the object”, that implicated on the analysis of the characteristics as dimensions, number of pages, paper quality, color applications and graphic nicety; (8) the possibilities of diversification of public established by a language with ability to speak simultaneously with children, with adults treated as children and adults through the children; (9) the confrontation among the booklets and its two book versions – 1924 and 1930; (10) the comparison among the different versions of the booklets as a result of the changes of illustrators, the plot change in 1940, the inclusion of brands to be advertised, the reduction of pages, the adaptation of the booklet for spelling booklets and comics formats; (11) the checking of dates and circulation data with a projection of a doable number of impressions; (12) the results obtained by the advertiser; (13) the possible “modes of reading” by Jeca Tatuzinho in its different periods in view of its content at the same time fun and instructive; (14) the adjustment and maladjustment among ways to read the Jeca recomposed by Lobato and the hillbilly imagery